A combination of hepatic encephalopathy and body mass index was associated with the point of no return for improving liver functional reserve after sofosbuvir/velpatasvir treatment in patients with hepatitis C virus‐related decompensated cirrhosis. Issue 1 (20th September 2022) - Sano, Tomoya; Amano, Keisuke; Ide, Tatsuya; Yokoyama, Keiji; Noguchi, Kazunori; Nakamura, Hiroki; Isoda, Hiroshi; Ohno, Miki; Shirachi, Miki; Morita, Yasuyo; Yano, Yoichi; Sumie, Shuji; et al.
Abstract: Aims: The real‐world efficacy of sofosbuvir/velpatasvir treatment for patients with hepatitis C virus‐related decompensated cirrhosis is unclear. We aimed to identify factors that improve liver functional reserve after treatment. Methods: This was a multicenter retrospective study of 12‐week sofosbuvir/velpatasvir treatment. A total of 48 patients with Child–Pugh (CP) class B or C were enrolled at 11 institutions. We evaluated changes in liver functional reserve at 24 weeks post‐treatment. Results: At baseline, 40 and eight patients were CP class B and C, respectively. The overall rate of sustained virologic response 12 weeks post‐treatment was 95.8% (46/48). Serum albumin, alanine aminotransferase and α‐fetoprotein levels, and the FIB‐4 index were significantly improved post‐treatment ( P < 0.05). Among patients who achieved sustained virologic response 12 weeks post‐treatment, those with CP class A increased from 0 to 24 patients (56%) at 24 weeks post‐treatment. In multivariate analysis, body mass index (BMI) ≥25 was an independent factor that inhibited CP class improvement ( P < 0.05). In decision tree analysis, after treatment, the initial divergent variable for CP class improvement was hepatic encephalopathy, followed by serum sodium level and BMI. Conclusion: Sofosbuvir/velpatasvir treatment improved the liver functional reserve in patients with hepatitis C virus‐related decompensated cirrhosis at 24 weeks post‐treatment. However, BMI ≥25 inhibited improvement in CP class. Additionally, decision tree analysis revealed that a combination of hepatic encephalopathy, serum sodium levels, and BMI were diversity profiles associated with no improvement in liver functional reserve after the treatment.